An investigation of archean and paleoproterozoic metamorphic processes in the Limpopo belt via detailed analysis of reaction textures in metapelites from the Bandelierkop Formation, Southern Marginal Zone of the Limpopo belt - Madlakana, Nonkuselo (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.